Inventare sakraler und profaner Schätze verwitweter Fürstinnen aus dem Hause Wittelsbach - Carola Fey (Österreichische Zeitschrift für Geschichtswissenschaften, 2022)
From late medieval princely courts, only a few written inventories of sacred objects have survived. Several list-shaped records can be found in foundation letters and wills. Only a few sources come from religious institutions. Thus these different types of texts must be consulted for the investigation of the material sacred culture of the courts and the pious practice of the princesses who used the inventoried objects. Two lists of possessions of widowed Wittelsbach princesses produced after their death, one at the beginning of the fifteenth century, the other in 1520, will be analysed in a comparative study. The article focuses on special text characteristics and possible interpretations by contextualizing the inventories with other sources.